The experience of two-dimensional magnetovariance modeling in the area of UAAS "Academician Vernadsky" (West Antarctic Peninsula) - I. M. Logvinov; V. N. Tarasov; S. S. Chulkov (Геофизический журнал, 2012)
For the first time for the waters of the Antarctic Peninsula, quantitative assessment of the distribution of geoelectric parameters of sea water, both in space and depth, as well as of a layer of sediment presumably of Cenozoic era, lying directly under the water has been given. This layer according to the seismic method of reflected waves is widespread in the continental shelf waters. Availability under the top layer of the older sedimentary rocks is still quite unknown. According to seismic and geo-electric methods at the present level of knowledge the existence of such sediments is expected both in shelf zone of the Bellingshausen Sea, and in the Larsen sedimentary basin. Based on the estimates of geoelectric parameters a map of the total longitudinal conductivity of sedimentary cover of M 1 : 10 000 000 of the region has been compiled for the first time. Magnetovariational parameters on the profile, crossing the Antarctic archipelago of islands have been given, which have shown that the conductive structures, which determine their behavior have a strike, coinciding with the strike of isobaths. To determine the capacity of geoelectrical methods for studying the deep structure of the region calculations have been made of interpretational parameters of magnetotelluric field by numerical simulation of twodimensional model along the profile of the valley of the Bellingshausen Sea to the kettle of the Weddell Sea, in which the distribution of geoelectric parameters of the sedimentary cover has been specified with the highest adequacy. Calculations have shown that the observed experimental data do not completely satisfy the model calculations. This fact gives grounds to hope that at least in the areas adjacent to Graham Land, geoelectrical investigations will facilitate studies of the deep structure of the regions.